Associations between loot box use, problematic gaming and gambling, and gambling-related cognitions. (September 2019) - Brooks, Gabriel A.; Clark, Luke
Abstract: Loot boxes are virtual goods in video games that produce randomly-generated in-game rewards, and have attracted scrutiny because of a resemblance to gambling. This study tests relationships between gaming involvement, engagement with loot boxes, and their associations with disordered gambling and gambling-related cognitions. Online questionnaires were completed by 144 adults via MTurk (Study 1) and 113 undergraduates (Study 2). Gaming and loot box-related variables included estimated time spent gaming and monthly expenditure, the Internet Gaming Disorder Scale (IGDS), and questions that assessed perceptions and behaviours related to loot boxes. Most participants thought loot boxes were a form of gambling (68.1% & 86.2%). A subset of items were condensed into a unidimensional "Risky Loot-box Index" (RLI) via exploratory factor analysis. In Study 1, the RLI showed significant associations with the Problem Gambling Severity Index ( r = .491, p < .001) and the Gambling Related Cognitions Scale ( r = .518, p < .001). Overall, gambling-related variables predicted 37.1% ( p < .001) of the variance in RLI scores. Findings were replicated, though attenuated, in Study 2. These results demonstrate that besides the surface similarity of loot boxes to gambling, loot box engagement is correlated with gambling beliefs and problematic gambling behaviour in adult gamers. Highlights: The majority of video game players are familiar with, and have used, Loot Boxes. Most gamers agreed with the statement that Loot Box are a form of gambling. Risky Loot Box use correlated moderately with gambling-related measures. Gambling-related variables predicted 37.1% of the variance for risky Loot Box use.